Injury and Mortality Profiles in Level II and III Trauma Centers. Issue 1 (January 2022) - Farhat, Ali; Grigorian, Areg; Farhat, Ahmed; Chin, Theresa L.; Donnelly, Megan; Dolich, Matthew; Kuza, Catherine M.; Lekawa, Michael; Nahmias, Jeffry
Background: While the benefit of admission to trauma centers compared to non-trauma centers is well-documented and differences in outcomes between Level-I and Level-II trauma centers are well-studied, data on the differences in outcomes between Level-II trauma centers (L2TCs) and Level-III trauma centers (L3TCs) are scarce. Objectives: We sought to compare mortality risk between patients admitted to L2TCs and L3TCs, hypothesizing no difference in mortality risk for patients treated at L3TCs compared to L2TCs. Methods: A retrospective analysis of the 2016 Trauma Quality Improvement Program (TQIP) database was performed. Patients aged 18+ years were divided into 2 groups, those treated at American College of Surgeons (ACS) verified L2TCs and L3TCs. Results: From 74, 486 patients included in this study, 74, 187 (99.6%) were treated at L2TCs and 299 (.4%) at L3TCs. Both groups had similar median injury severity scores (ISSs) (10 vs 10, P < .001); however, L2TCs had a higher mean ISS (14.6 vs 11.9). There was a higher mortality rate for L2TC patients (6.0% vs 1.7%, P = .002) but no difference in associated risk of mortality between the 2 groups (OR .46, CI .14-1.50, P = .199) after adjusting predictors of mortality. L2TC patients had a longer median length of stay (5.0 vs 3.5 days, P < .001). There was no difference in other outcomes including myocardial infarction (MI) and cerebrovascular accident (CVA) ( P > .05). Discussion: Patients treated at L2TCs had a longer LOS compared to L3TCs. However, after controlling for covariates, there was no difference in associated mortality risk between L2TC and L3TC patients.